Characterization of Pinilisa Dance Using the Dance Protocol as Performed by A Local Community in Isabela - Guado, Mark Jason D. (Future Science / FSH-PH Publications, 2024)
This study aimed to characterize the Pinilisa dance using the dance protocol as performed by a local community in Isabela and to create instructional materials as well as to improve the Pinilisa dance movement. Using ethnographic and narrative inquiry in the data gathering through a Focus Group Discussion (FGD), observation, structured interview guide, and documentation, this study documented, notated, and analyzed the Pinilisa dance as a reflection of the Ilocano culture, as well as the costumes, props, accessories, movement or dance pattern, dance notation, staging (formation) and performance, music notation, and sequencing to facilitate the development of supplemental instructional materials in teaching folk dance in Grade 7 Physical Education subject. This study's key informants were the residents and government employees of Jones, Isabela who are knowledgeable about the Pinilisa dance, including the municipal vice-mayor, municipal administrator, tourism officer, festival organizer, selected Local Government Units (LGUs), choreographers, and PE teachers. This study revealed that Pinilisa dance is an expression of Ilocano culture emphasizing five aspects: political, social, physical, economic, and religious. It is a dance that celebrates the abundant harvest of Pinilisa rice, from planting and harvesting to selling, honoring its people and expressing gratitude for the year's abundant crop. It embodies the Ilocano values of being hard-working, industrious, family-oriented, bayanihan, cheerful, resilient, and God-fearing, which reflects the people of Jones. The instructional materials in which the documented Pinilisa dance is an input for significant use in PE class in Grade 7, particularly in teaching folk dance. It is an additional instrument for uplifting, preserving, and promoting Jones, Isabela's cultural heritage.